PELATIHAN KETERAMPILAN MENYULAM BAGI SISWA MADRASAH ALIYAH AL- ALAWIYAH KRANJI, BEKASI - Wina Yuliana; Rini Endah Sugiharti; Yudi Budianti (An-Nizam, 2022)
This training activity aims to increase creativity in the embroidery skills of the students of Madrasah Aliyah Al-Alawiyah Kranji. This activity was carried out offline for 3 days on 22-25 February 2022 with a training method. With embroidery skills training for 11th grade students of Madrasah Aliyah Al-Alawiyah Kranji, students can learn basic techniques in embroidery, develop creative and innovative ideas in designing or drawing patterns on fabrics before embroidering. In addition, the work of this embroidery skill can be sold to improve the economy of the surrounding community.